Job Satisfaction of School Library Professionals: A Case Study of Asansol Sub-division - Mondal, Debdas (Journal of Information and Knowledge, 2020)
A school library caters to the young minds. The level of job satisfaction among school librarians is an important issue. The present study seeks to examine the level of job satisfaction of school librarians. The sub-divisional area of Asansol in West Bengal has been selected for this case study. This study shows a significant link between satisfaction and dissatisfaction of school librarians in the mentioned area.